Telaah Term Millah â€˜Abd Al-Muá¹á¹alib dalam Hadis Riwayat Ibn Hibban no. 982 dan Kaitannya dengan Persoalan Keimanan Abu Thalib - Ilmiyah, Dakhirotul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Study of Term Millah 'Abd Al-Muá¹á¹alib in the Hadith Narrated by Ibn Hibban no. 982 and its Relation to the Problem of Abu Talibâ€™s FaithAbu Talib's problem is centered on the issue of faith or disbelief. Some scholars are of the opinion that Abu Talib was a disbeliever because until the end of his life he was reluctant to pronounce the shahada. However, some argue that Abu Talib is a believer because of his great care and love for the Prophet Muhammad so that Allah glorifies him. In this regard, in the hadith narrated by Ibn á¸¤ibbÄn it is stated that Abu Talib died holding fast to millah 'Abd al-Muá¹á¹alib. With this, this study aims to examine more deeply the meaning of millah 'Abd al-Muá¹á¹alib in the hadith narrated by Ibn á¸¤ibbÄn no. 982 as one of the efforts to strengthen the argument that Abu Talib died in a state of faith. This research is a type of qualitative research with the type of library research. The results of this research show that the meaning of Millah 'Abd al-Muá¹á¹alib contained in the hadith narrated by Ibn á¸¤ibbÄn no. 982 which has the meaning of monotheism religion. In this case, it means that Abu Talib is a follower of the hanif religion which unites Allah SWT, as adhered to by his father Abdul Muttalib. Abu Talib believed in his heart that he justified Islamic teachings, but he never professed his faith with the intention of protecting the Prophet Muhammad from the heinous acts of the Quraysh infidels. So that Abu Talib was classified as a believer in his lifetime until the end of his life, and not a disbeliever